2016
DOI: 10.4081/ni.2016.6677
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary neuropathy with liability to pressure palsies: a single-center experience in southern Brazil

Abstract: The spectrum of clinical and electrophysiological features in hereditary neuropathy with liability to pressure palsies (HNPP) is broad. We analyze a series of Brazilian patients with HNPP. Correlations between clinical manifestations, laboratory features, electrophysiological analyze, histological and molecular findings were done. In five cases, more than one episode occurred before diagnosis. Median nerve in the carpal tunnel at the wrist, ulnar nerve in its groove at the elbow, fibular nerve in the head of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
2
2
0
1
Order By: Relevance
“…In case 4, the patient had a very uncommon suprascapular neuropathy which is not usually observed in HNPP. Recent studies have reported a few cases of suprascapular neuropathy in its notch at the supraspinatus fossa caused by strenuous physical activities; this correlates with our patient who also experienced arm weakness after strenuous exercise during his military service [ 13 ].…”
Section: Discussionsupporting
confidence: 84%
“…In case 4, the patient had a very uncommon suprascapular neuropathy which is not usually observed in HNPP. Recent studies have reported a few cases of suprascapular neuropathy in its notch at the supraspinatus fossa caused by strenuous physical activities; this correlates with our patient who also experienced arm weakness after strenuous exercise during his military service [ 13 ].…”
Section: Discussionsupporting
confidence: 84%
“…It is noteworthy the intra-familial phenotypical heterogeneity, as previously reported. 1,[3][4][5] To summarize, current literature emphasizes the presence of atypical forms of HNPP, as observed in our group of patients. The related absence of clinicalelectrophysiological correlation highlights the importance of nerve conduction studies and genetic study for the definite diagnosis of the disease.…”
Section: Discussionsupporting
confidence: 68%
“…These phenotypes include Charcot-Marie-Tooth-like (CMT-like) polyneuropathy, chronic sensory polyneuropathy, progressive mononeuropathy, recurrent positional short-term sensory symptoms and presenting symptoms mimicking a Guillain-Barré syndrome. [1][2][3][4][5] Therefore, in the diagnostic evaluation of HNPP, neurophysiological and genetic testing are essential. [1][2][3] Electrophysiologically, the most common findings are abnormal sensory responses (absent or with low amplitude with prolonged latency), prolonged distal motor latencies with normal or slightly diminished conduction velocities (CV), and CV slowing, in the range of demyelination (<39 m/s), at normal sites of entrapment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os pacientes com HNPP apresentaram, na grande maioria dos casos (32 pacientes -94.0%), o padrão de neuropatia sensitivo-motora assimétrica com alentecimento focal da condução (NSMAAF), semelhante aos achados prévios da literatura (PAREYSON et al, 1996;MOUTON et al, 1999;LORENZONI et al, 2016;ROBERT-VARVAT et al, 2018 RAMADAN et al, 2001;JACOBSON, 2005).…”
Section: Estudos Da Condução Nervosaunclassified